PENGGUNAAN ALAT PELINDUNG DIRI (APD) DAN LAMA KERJA PADA KEJADIAN KECELAKAAN KERJA PENGUMPUL SAMPAH - Silaban, Marlis; yusmidiarti, yusmidiarti (JURNAL MEDIA KESEHATAN, 2014)
Based on the results of the data obtained from the Parks Department and the Health of Bengkulu in 2013 produced garbage 291 m3/day. and the number of officers in the waste collection market Bengkulu City numbered 40 officers of garbage collectors. The purpose of this research was to determine the relationship of the application of personal protective equipment and length of employment with the incidence of occupational accidents in the garbage collector. This research used an analytical survey research methods, with a cross-sectional design. The sample was a total sampling of 40 people. Analysis used chi square with α = 0.05. The results showed no significant relationship between the application of personal protective equipment in work accident at a garbage collector (p=0.034 and OR=7.46) and there were a significant relationship between length of employment with the incidence of occupational accidents at waste collection (p=0.001 and OR=37.50).